Aturan Dan Tradisi Lokal: Pelestarian Hutan Oleh Masyarakat Adat Di Kabupaten Luwu Utara - Nardy Najib; Maria Maria; Luthfi Hanindityasari; Dinda Sari (Jurnal Ilmu Sosial dan Humaniora, 2024)
Sassa Village is one of the villages closest to the forest area, and it has a relationship between the community and the forest. Around the Sassa protected forest are local communities, namely the To Limola indigenous people, in Sassa hamlet and Makumpa hamlet. The indigenous people of To Limola still uphold the beliefs of customs that are still strong. The main objective of this study is to identify the form of local wisdom of the To Limola indigenous people in the use of timber and non-timber forest products (NTFPs). The method used is Snowball Sampling, whose informant data includes the To Limola Indigenous people who live around the Sassa Protected Forest area, especially in Sassa Hamlet and Makumpa Hamlet. The respondents consisted of 20 people. The community's local wisdom consists of norms, customary laws, and punishments for managing forest resources, and the To Limola customary institution's structure comprises the gathered data. The native inhabitants of To Limola are fully aware of the need to preserve and safeguard forest regions, particularly those that are indigenous and protected. Using wood forest products for fuel and medicinal purposes is one way. In addition, the community manages and uses non-timber forest products (NTFPs), which include fruit, honey, bamboo, rattan, palm, and turmeric. The indigenous To Limola people also follow customs about social institutions while using forest resources. Examples of these customs include prohibiting burning wasps in forested areas, cutting down bamboo shoots, and gathering bamboo shoots in forested areas designated as protected forests. Limola traditional leaders are very strict about local cultural values because there are many traditional norms regarding conservation obligations in maintaining the forest. These rules are mandatory and must never be violated within the custom scope. For the Limola indigenous people, forests have a vital role in life. If the forest continues to be protected, it will not damage people's lives, but the forest will serve its contents well for human needs.